2019
DOI: 10.1158/1055-9965.epi-19-0128
|View full text |Cite
|
Sign up to set email alerts
|

Pretreatment Dietary Patterns Are Associated with the Presence of Nutrition Impact Symptoms 1 Year after Diagnosis in Patients with Head and Neck Cancer

Abstract: Background: Dietary inflammatory potential could impact the presence and severity of chronic adverse treatment effects among patients with head and neck cancer. The objective of this study was to determine whether pretreatment dietary patterns are associated with nutrition impact symptoms (NIS) as self-reported 1 year after diagnosis. Methods: This was a longitudinal study of 336 patients with newly diagnosed head and neck cancer enrolled in the University of Michigan Head and Neck Specialized Program of Resea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 35 publications
0
11
0
Order By: Relevance
“…First, the present analysis utilized pretreatment values for the consumption of dietary fiber and whole grains, which fails to take into account the dynamic nature of dietary patterns over time. It is possible that fiber consumption may decrease during and after cancer treatment in many patients as a result of disease- and treatment-related symptoms that may negatively affect the ability or desire to consume fibrous foods [23,42]. Second, our dataset lacked information on food sources of fiber (e.g., cereal-, fruit-, or vegetable-derived).…”
Section: Discussionmentioning
confidence: 99%
“…First, the present analysis utilized pretreatment values for the consumption of dietary fiber and whole grains, which fails to take into account the dynamic nature of dietary patterns over time. It is possible that fiber consumption may decrease during and after cancer treatment in many patients as a result of disease- and treatment-related symptoms that may negatively affect the ability or desire to consume fibrous foods [23,42]. Second, our dataset lacked information on food sources of fiber (e.g., cereal-, fruit-, or vegetable-derived).…”
Section: Discussionmentioning
confidence: 99%
“…An additional item, assessing the burning pain and discomfort that characterizes mucositis, was included and extracted from the pain domain of the questionnaire. Mucositis has been shown to impact dietary intake and thus was included in the analysis for this reason [ 9 , 26 ]. Responses to each of these individual items were dichotomized into categories “not at all bothered” and “slightly to extremely bothered”, as was previously done by members of our research team [ 27 ].…”
Section: Methodsmentioning
confidence: 99%
“…The report by Ganzer et al found that NIS, including dysphagia, xerostomia, and altered taste, persisted after three years postchemotherapy in a mixed-methods study of 10 long-term HNSCC survivors [ 8 ]. Chronic NIS may pose significant nutritional consequences, including reduced nutrient intake and impaired nutritional status, which is noteworthy, given that this population is disproportionately affected by high rates of cancer cachexia [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations